Editorial: Towards a better understanding of the correlation between the subsidence pattern and land use type - Du, Zheyuan; Hay-Man Ng, Alex; Ge, Linlin (Frontiers in Earth Science, 2024)
The rapid advancement in geospatial technologies continues to push the boundaries of environmental monitoring and infrastructure management [1][2][3][4]. This special issue presents five cutting-edge studies that explore various aspects of geodetic monitoring, from landslide susceptibility and road extraction to the impacts of climate change on nutrient pollution, urban subsidence, and insulator defect detection. Employing advanced machine learning algorithms and geospatial analysis, these studies offer significant insights into sustainable land-use practices, hazard management, and the precision monitoring of infrastructure health.